No Way Out or No Way In? The Effect of Standardization, Licensing, and Skills Specificity of the Initial and Target Occupations on Status Mobility - Basha Vicari; Stefanie Unger (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2020)
Occupational mobility is becoming increasingly important today owing to technological change and changing requirements in the employment system. This article examines the extent to which institutional characteristics of occupations hamper intragenerational occupational mobility on the labor market. By combining data from the Adult Cohort of the German National Educational Panel Study (NEPS) with occupational information from the German Federal Employment Agency, we test the power of the characteristics of the initial and target occupations to explain horizontal and vertical status mobility. The occupational characteristics that we focus on are the standardization of certificates, occupational licensing, and the specificity of skills. Using multinomial logistic regression, we find that both initial and target occupations with such characteristics might generate mobility constraints and impede the correction of a~disadvantageous starting position. Status increases are mainly possible from standardized to nonstandardized, from specific to nonspecific and, in some instances, from nonlicensed to licensed occupations.
Keywords: 300; Occupational mobility; Occupational characteristics; Status increase; Target job; NEPS; Berufsmobilität; Berufsmerkmale; Sozialer Aufstieg; Zielberuf; NEPS